PENGARUH TEKNIK EFFLEURAGE KOMBINASI OLIVE OIL JAHE (Zingiber officinale) TERHADAP DYSMENORHEA PADA REMAJA PUTRI - wanto, Su; Islamiyah, Mujtahidatul (Fakultas Ilmu Kesehatan Universitas Gresik, 2018)
ABSTRACTÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Puberty is a sexual maturity characterized by menarche. In this period have problems, is menstruation pain (dysmenorhea). One effective way to prevent menstruation pain (dysmenorhea) is relaxation in the form of a massage or hand massage. In addition, ginger (Zingiber Officinale) is also an herbal therapy that can smooth blood circulation and reduce pain. The purpose of this research is to determine the effect of Technique of Effleurage Combination Ginger Olive Oil to Dysmenorhea in Adolescents.This research method used pra experimental with the draft One-Group Pra-Post test Design. Sample was selected using the purposive sampling method. Sample obtained as manyÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â 18 peoples. The independent variable in this research was effect of technique of effleurageÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â combination ginger olive oil , while the dependent variable in this research is the decrease of pain (dysmenorhea) in adolescents. Data were collected through pre test and post test. Data analyze of the data used test statistic Wilcoxon Signed Ranks Test with significant value <0.05. The results of research showed the mean value of pre test = 3.22ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â and mean post test = 2.22, and significant value (2-tailed) = 0.000, where p = 0.000 <a (0.05). ItÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬ÃƒÂ¢Ã¢â‚¬Å¾Ã‚Â¢s mean there was effect of technique of effleurage combination ginger olive oil to dysmenorhea in adolescents.ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Technique of effleurage combination ginger olive oil can be used as ners preneur to help reduce the intensity of menstruation pain from the moderate category to light category.Keywords: Primary Dysmenorhea, Technique of Effleurage, Ginger.DOI:ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â 10.5281/zenodo.1401004